The Influence of Islamic Work Ethics and Job Satisfaction on Organizational Citizenship Behavior through Organizational Commitment - Hary Sulaksono; Mohd Farid Shamsudin; Tamriatin Hidayah (ABM: International Journal of Administration, Business and Management, 2023)
This research aims to analyze the influence of Islamic work ethics and job satisfaction on organizational citizenship behavior both directly and through organizational commitment. The research was carried out at SMA Muhammadiyah 3 Jember. This type of research is included in the type of quantitative research. The sample used was 4 4 respondents with a saturated sampling technique. The data analysis method used is the Partial Least Square (PLS) Data Analysis method. The research results show that there is an influence between Islamic Work Ethics on Organizational Commitment and Organizational Citizenship Behavior. There is also an influence between Job Satisfaction on both Organizational Commitment and Organizational Citizenship Behavior. Organizational Commitment is not able to act as a mediation linking Islamic Work Ethics to Organizational Citizenship Behavior, but it can act as a mediation linking the influence of Job Satisfaction on Organizational Citizenship Behavior. Organizational Commitment influences Organizational Citizenship Behavior.